Pengaruh Service Environment, Customer Knowledge, Dan Customer Relation Management Terhadap Service Quality Dan Dampaknya Terhadap Brand Equity - Verry Wijaya dan Chairy (Universitas Tarumanagara, 2019)
This study aims to determine the effect of service environment, customer knowledge, and customer relations management on service quality and its impact on brand equity at PT. XYZ. In addition, it can provide input to the company regarding the brand equity of the private brand of PT. XYZ and can help companies in designing the right and effective marketing strategy planning so that the company can survive in the retail world competition in the modern market. This study uses qualitative methods and is included in survey research. The data to be taken is primary data obtained through interviews with visitors to PT. XYZ uses a questionnaire. The population in this study is the consumer respondents in one of the outlets PT. XYZ in Jakarta. The sampling technique is probability sampling with the sample criteria used are respondents from consumers. Because the population in the study is unknown, the number of samples used in this study is 100-150 respondents where the number of respondents obtained the number of indicators in the research questionnaire (Hair et.al 2016, p.102). Analysis of the data in this study using this type of analysis Structure Equation Model (SEM) with the help of the program AMOS 18. The results showed that the service environment had a positive relationship but did not have a significant effect on service quality..